Accessiblility and Health Needs for Maternal and Child Health Services in Primary Care Unit among Urak Lawoi’s Women in a Southern Island, Thailand - Aramsritam, Jittima; Lymchaiarungruang, Sawitri; Singchungchai, Pechnoy (Journal of Health Science of Thailand, 2017)
This qualitative study was aimed at describing accessibility, needs, and barriers of accessibility to maternal and child care at a nearby primary care unit (PCU) among Urak Lawoi women living on an island in southern Thailand. Fifteen participants with experience in receiving antenatal care and/ or birth delivery service at the PCU were recruited through snowball technique. The data were collected using in-depth interview and non-participatory observation. Methodical triangulation was adopted to ensure data validity and content analysis was carried out. The results revealed that before 2005 they could access to antenatal care and postnatal care but not labor care in PCU. After 2005 the PCU provided complete service in antenatal care, labor care and postnatal care by a professional nurse. The factors enhancing accessibility were: 1) location 2) affordable health fee 3) satisfaction with professional behavior and services, 4) integrated system of traditional and modern health care. Their needs for maternal and child care were expressed in four aspects: 1) reliable services (availability, health information, and one stop service), 2) reliable providers (knowledge, behavior, and skill), 3) referral system and 4) reliable medical equipment. Barriers to the health service accessibility were found in three aspects: 1) unreliable services (data on health services were not thorough and sufficient, and poor referral system; vehicle and network coordination); 2) unreliable health providers (knowledge and skill); and attitude toward the services (medication at the primary care unit was not of good quality; and provider gender); and 3) social and cultural. The study recommended a policy to improve health manpower knowledge and skills for improving the maternal and child health services in obstetrics deem appropriate to local context in term of belief, culture, integration of modern and traditional medicine, efficient referral system, and adequate equipment.